Fractures of the Whole: A Depiction of the shamanic universe on Kača drums brought by J.J. Sederholm from Siberia in 1917 - Victoria Soyan Peemot (Studia Orientalia Electronica, 2017)
This paper is a brief description of two drums brought back by the Finnish geologist Jacob Johannes Sederholm from his expedition to Siberia in 1917. These two drums have not previously been described in any scholarly work. Therefore, research on the drums, based on ethnographical sources and museum collections, was done to identify their provenance.